Effect of taking an online Agroindustry course on student learning at the Costa Rican Distance Education University (UNED Research Journal, 2010)
Learning online is a challenge that is becoming common around the world, for study and work. The Costa Rican Distance Education University is motivating students to learn through this system. Agroindustry was the first course in the agronomy career that was taught online. To study the effect of the online modality on learning, the course contents were adapted for online teaching and the students performance and opinion about the course were recorded. The evaluation and learning were positive: Agroindustry can be successfully taught in this university using online materials.
Keywords: Agro-industry; virtual; traditional; performance; acceptance; motivation; learning evaluation.